2018
DOI: 10.1111/bju.14150
|View full text |Cite
|
Sign up to set email alerts
|

Variability and interpretation of communication taxonomy during robot‐assisted surgery: do we all speak the same language?

Abstract: To our knowledge, this is the first study to provide a detailed analysis of communication during RAS. It lays a foundation for standardized taxonomy to improve communication, surgical efficiency and patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 23 publications
0
27
1
Order By: Relevance
“…Several of the included studies were conducted by the same research group (i.e., overlapping authors). Five studies investigating communication that came from the same research group were included in this review (Raheem et al, 2018; Sexton et al, 2018; Tiferes, Bisantz, et al, 2016, 2019, Tiferes, Hussein, et al, 2016): these articles were used to identify communication requirements and patterns during robotic-assisted surgery. Communication was also investigated during open and laparoscopic procedures in work by Sevdalis et al (2007, p. 2012), who used frequency of communication events to quantify case-irrelevant conversations and overall communication in the OR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of the included studies were conducted by the same research group (i.e., overlapping authors). Five studies investigating communication that came from the same research group were included in this review (Raheem et al, 2018; Sexton et al, 2018; Tiferes, Bisantz, et al, 2016, 2019, Tiferes, Hussein, et al, 2016): these articles were used to identify communication requirements and patterns during robotic-assisted surgery. Communication was also investigated during open and laparoscopic procedures in work by Sevdalis et al (2007, p. 2012), who used frequency of communication events to quantify case-irrelevant conversations and overall communication in the OR.…”
Section: Resultsmentioning
confidence: 99%
“…Although observer dependent, such studies were included in this review as they quantified communication metrics. Studies reported a range of agreement between 0.74 and 0.98 (Keller et al, 2016; Raheem et al, 2018; Sevdalis et al, 2012; Sexton et al, 2018; Tiferes, Bisantz, et al, 2016, p. 10; Tiferes et al, 2019; Weigl et al, 2018), which is typically considered as substantial agreement (McHugh, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Presently, traditional systems use rigid suction cannulas that make access to some narrow spaces difficult while also demanding good communication between surgeon and a skilled bedside assistant. 10,11 An articulating robotic instrument for suction was introduced for the da Vinci Si robot in 2013 with the same instrument also currently available on the Xi robot, but there has not been any significant adoption most likely because this occupies one of the four robotic arms that could be used for other instruments.…”
Section: Discussionmentioning
confidence: 99%
“…All were published between 2004 and 2020 (median: 2017). Eleven studies were conducted in the US, [15,17,[27][28][29][30][31][32][33][34][35], six in the UK [18,[36][37][38][39][40], and four in Western/Northern European countries [22,[41][42][43]. Studies either examined one [18,22,28,32,41] or several OR professions [15, 17, 27, 29-31, 33-40, 42, 43].…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%